Koagulanty wstępnie zhydrolizowane = Prehydrlysed coagulants - Krupińska, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the prehydrolyzed coagulants with particular emphasis on polyaluminium chloride. The paper presents methods of their production. In the article are characterized forms of aluminum present in the prehydrolyzed coagulants solutions with particular emphasis on Al13 polymer.
Keywords: koagulacja; chlorki poliglinu; alkaliczność koagulantu; coagulation; polyaluminium chlorides; alkalinity of coagulant